The Relationship Between Health-Related Physical Fitness and Psychological Health of Retired Martial Arts Athletes - Nurhidayah, Dewi (Universitas Negeri Jakarta, 2025)
This study used a survey approach to determine the fitness and health conditions of retired martial artists and the relationship between the two. A total of 33 subjects, consisting of 17 retired male martial artists and 16 retired female martial artists, participated in this study. The instruments used in this study were a fitness test battery and the General Health Questionnaire 12 (GHQ-12). The fitness test battery consisted of five test items, namely Body Mass Index (BMI), sit and reach (flexibility), 1-minute push-ups (arm and chest muscle strength), 1-minute sit-ups (abdominal muscle strength), and a 12-minute run (cardiovascular endurance). The data analysis techniques in this study used descriptive statistics, percentage formulas, and correlations. The analysis was performed using MS Excel and JASP. Nearly half of retired martial artists, both female and male, had poor physical fitness levels, while the majority of retired martial artists showed signs of psychological distress. There is a relationship between fitness levels and the psychological health of retired martial artists. The results of this study indicate the importance of developing educational programs for retired athletes to maintain physical fitness and psychological health in future studies.